2020
DOI: 10.30996/anaphora.v3i1.3642
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Translation Techniques in Translating Cultural Words in the Da Vinci Code Novel From English Into Bahasa Indonesia

Abstract: The purpose of this study is to identify techniques of translation that are applied in translating cultural words in The Da Vinci Code novel from English into Bahasa Indonesia and interpreting the reason of the translator in applying those techniques. This study uses descriptive and qualitative approach. The cultural words found in the novel were collected in tables and categorized based on five types of culture that are proposed by Newmark. Result of the study shows that there are 171 cultural terms and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
1
Order By: Relevance
“…The translation technique with highest occurrence found in this study differs from the result of previous research (Anwar et al, 2020;Kuswahono, 2020;Sodiq et al, 2020). Studies by those researchers stated that the translation technique that occurred the most in the texts they analyzed were linguistic compression (Anwar et al, 2020), which was not identified at all in the analyzed abstracts of this research, and pure borrowing (Kuswahono, 2020;Sodiq et al, 2020). On the other hand, Al Farisi's ( 2020) findings shows a similarity to this study's.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The translation technique with highest occurrence found in this study differs from the result of previous research (Anwar et al, 2020;Kuswahono, 2020;Sodiq et al, 2020). Studies by those researchers stated that the translation technique that occurred the most in the texts they analyzed were linguistic compression (Anwar et al, 2020), which was not identified at all in the analyzed abstracts of this research, and pure borrowing (Kuswahono, 2020;Sodiq et al, 2020). On the other hand, Al Farisi's ( 2020) findings shows a similarity to this study's.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of their study showed that linguistic compression was used the most prominently at 56.52%, while other techniques occurred less frequently (10% and below). Kuswahono (2020) used the technique to identify translation techniques of a novel. His study revealed that six techniques were employed.…”
Section: Introductionmentioning
confidence: 99%